Pemanfaatan Limbah Pelepah Siwalan (Borassus flabellifer) menjadi Briket Bahan Bakar Tungku - I Wayan Roli Arta; I Putu Surya Wirawan; Ni Luh Yulianti (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2025)
Palm tree fronds are a cellulose material that is suitable for use as a basic material for making briquettes.The aim of this research is to obtain the characteristics of briquettes from siwalan frond charcoal withdifferent mesh sizes and adhesive percentages and to obtain treatment parameters that produce the bestquality siwalan frond briquettes. In this research, a Randomized Group Design (RAK) experimentaldesign was used with two factors. The first factor is the variation in mesh size which consists of 3 meshvariations (S1: 60 mesh, S2: 80 mesh) and the second factor is the adhesive percentage which consists of5 variations (M1: 30%, M2: 35%, M3: 40%, M4: 45%, M5: 50%. By combining this experimental designwhich was repeated twice, 20 repetition samples were obtained. The parameters that are focused on in thisresearch are the amount of water content, the amount of ash content, compressive strength, density andcombustion rate. The results of this research are that there is a significant interaction between charcoalparticle size and adhesive percentage on parameters such as water content, ash content, compressivestrength, density and burning rate. The best treatment was obtained using 80 mesh size and an adhesivepercentage of 50%, water content with a value of 6.66%, ash content with a value of 4.35%, compressivestrength of 64.16 N, mass density with a value of 0.43 g/cm³ and combustion rate with a value of0.107gr/minute.